The complete mitochondrial genome of Sinojackia microcarpa: evolutionary insights and gene transfer - Tailin Zhong; Shijie Huang; Rongxiu Liu; Juan Zhuo; Haifei Lu; Chunlin Gan; Jun Fu; Qixia Qian (BMC Genomics)
Abstract Background As a dicotyledonous plant within the Styracaceae family, Sinojackia microcarpa (S. microcarpa) is notable for its library-shaped fruit and sparse distribution, serving as a model system for studying the entire tree family. However, the scarcity of genomic data, particularly concerning the mitochondrial and nuclear sequences of S. microcarpa, has substantially impeded our understanding of its evolutionary traits and fundamental biological mechanisms. Results This study presents the first complete mitochondrial genome sequence of S. microcarpa and conducts a comparative analysis of its protein-encoding genes across eight plant species. Our analysis revealed that the mitochondrial genome of S. microcarpa spans 687,378 base pairs and contains a total of 59 genes, which include 37 protein-coding genes (PCGs), 20 transfer RNA (tRNA) genes, and 2 ribosomal RNA (rRNA) genes. Sixteen plastid-derived fragments strongly linked with mitochondrial genes, including one intact plastid-related gene (rps7), were identified. Additionally, Ka/Ks ratio analysis revealed that most mitochondrial genes are under purifying selection, with a few genes, such as nad9 and ccmB, showing signs of relaxed or adaptive evolution. An analysis of twenty-nine protein-coding genes from twenty-four plant species reveals that S. microcarpa exhibits a closer evolutionary relationship with species belonging to the genus Camellia. The findings of this study provide new genomic data that enhance our understanding of S. microcarpa, and reveal its mitochondrial genome’s evolutionary proximity to other dicotyledonous species. Conclusions Overall, this research enhances our understanding of the evolutionary and comparative genomics of S. microcarpa and other plants in the Styracaceae family and lays the foundation for future genetic studies and evolutionary analyses in the Styracaceae family.